USER INVOLVEMENT IN INFORMATION SYSTEM QUALITY - Rapina, Rapina; Carolina, Yenni; Joni, Joni; Anggraeni, Silvia (International Journal of Innovative Technologies in Social Science, 2022)
system is the effectiveness of a user to understand the information system and implement the use of technology. One of the factors that can affect the quality of accounting information systems is user involvement, which will be the independent variable in this study. The purpose of this study was to examine and analyze the effect of user involvement on the quality of information systems in SMEs in Indonesia. The primary data used in this study was obtained by distributing questionnaires to 78 SMEs who participated in filling out the questionnaire. In this study, the data were analyzed using the structural equation model-PLS. The results showed that user involvement has a significant effect on the quality of information systems.